Haematological and Biochemical changes in experimentally infected local chickens with biting lice - Fatima Ibrahim Mohammad; Hadi M.AL-Mayali (Al-Qadisiyah Journal of Pure Science, 2018)
The current study was designed to study the haematological and biochemical changes caused by experimentally infection with biting lice for the period from November 2013 to June 2014.                                                                                                                                                                30 bird were taken from the chickens local chicks Gallus gallus domesticus aged one week purchased from local markets of AL-Diwaniya city divided into three groups included of each 10 birds (two experimentally groups and one control group) it was hit by lice from naturally infected chickens and then measured blood and biochemical parameters changes at the end of experiment about seven months.                                                                                                                                                          The results showed of the blood parameters at end of the experiment significantly decreased  in the number of red blood cells2.29(x106/mm3), packed cell volume 37.99%, Haemoglobin 9.52(g/dl) and Mean corpuscular Haemoglobin concentration 29.09(g/dl) while showed significantly increased in Mean corpuscular volume 143.23(Âµ/m3), Mean corpuscular Haemoglobin 47.32(pg) and blood platelets24.36(x103/mm3), and the results showed significantly increased in white blood cells count144.05(x103/mm3),percentageMonocytes 9.10%, Eosinophils4.82%, Neutrophils2.80% and significantly decreased in percentage Lymphocytes67.43%.                                                                                   The results biochemical paramerters showed  significantly decreased in Glucose and Cholesterol concentration and significantly increased in uric acid and Total protein concentration and non-significantly increased in creatinin concentration.